Rotten Richie and the ultimate dare - Polacco, Patricia (New York : Philomel Books, 2006)
Richie and his younger sister Trisha face off in a contest to see whose hobby is more challenging.
School Library Journal.
Booklist.
Kirkus Review.
2.5
K-3
2.5.
Keywords: Contests -- Juvenile fiction; Hobbies -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Contests -- Fiction; Hobbies -- Fiction; Brothers and sisters -- Fiction; Humorous stories; Contests -- Fiction; Hobbies -- Fiction; Siblings -- Fiction; Humorous fiction; Humorous fiction